Inhaled nitric oxide theraphy in preterm infants with severe pulmonary distress syndrome - cases presentation - Mihaela Demetrian; Georgeta Grecu; Andreea Vidru; Andreea Calomfirescu-Avramescu; Alina Ciuca; Anca Panaitescu (Amaltea Medical Publishing House, 2020)
Respiratory failure in the premature newborn may be complicated by pulmonary hypertension (PAH) that does not always respond to conventional therapies. Conventional therapy for PAH involves: respiratory support, surfactant administration, sedation and / or muscle relaxation and inotropic agents in the most premature patients. Our experience in nitric oxide therapy in premature infants under 32 weeks dates back approximately 5 years. There were 7 cases of premature infants with respiratory failure who did not respond to conventional methods of therapy. We will present three case reports with hypoxic respiratory failure and severe pulmonary hypertension that responded favorably to nitric oxide therapy.